PENGARUH KEJELASAN SASARAN ANGGARAN DAN PARTISIPASI ANGGARAN TEHADAP KINERJA ORGANISASI DENGAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL PEMODERASI (STUDI PADA KELEMBAGAAN DAN UKM DI UST) - Intan Rohmah Saputri (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to test whether the clarity of budget targets and budget participation in institutions and Student Activity Units of the Sarjanawiyata Tamansiswa University Yogyakarta have an effect on organizational performance with leadership style as a moderating variable. The study took a sample of students who were active in the Student Activity Unit at the Sarjanawiyata Tamansiswa University, Yogyakarta. The technique used in sampling is carried out with a non-probability or non-random approach using convenience sampling. Data collection was carried out by spreading the google form link through the Instagram and Whatsapp applications to institutional members and the Student Activity Unit (UKM). The number of questionnaires processed is 100 questionnaires. Data were analyzed using path analysis. The results showed that the clarity of budget targets had no effect on organizational performance. Budget participation has an effect on organizational performance. Leadership style cannot strengthen the influence of clarity of budget objectives on organizational performance. Leadership style cannot strengthen the influence of budget participation on organizational performance. Keywords: Clarity of budget targets; Budget Participation; Organizational Performance; Leadership Style